Crédito, Estado e desenvolvimento: o direcionamento federal do crédito pela perspectiva do direito econômico - Sarai, Leandro (2017)
Given the importance of credit for economic development, this thesis sought to demonstrate the state action attached to it, mainly by earmark mechanism at the federal level, in addition to emphasizing the important role of public banks as instruments aimed at achievement of objectives of public interest. This research was justified by the scarcity of studies in Law about the subject providing a systematic and panoramic view of the most common forms of earmarked credit gathered in one body. This approach had the advantage of allowing the lifting of common points among the types of earmarked credit. It was justified also by the need to seek respect for the Constitution and the laws against simplistic views that preach practically the extinction of the state action in all that harms the capitalist accumulation or detrimental to the "free market forces", and due the fear that such claims lead to worsening social inequality. Based on these assumptions, and through legislative survey, some data and legal and economic literature, the thesis demonstrated the non-neutral character of credit, the importance of their proper destination, its peculiarity to function as infrastructure of economic activity, in addition to clarifying the concept of credit earmarking. It brought even a brief retrospect of the law evolution on the financial system and notes on the federal banks to demonstrate that their reason for being is not the pursuit of profit. Then it outlined the main features and critical of each type of earmarked credit: BNDES, real estate, rural and microfinance. At the end, without ignoring the critical and negative aspects of state action on credit, introduced the debate on such operations, but emphasizes that these disadvantages do not justify its extinction, but its improvement. To this end, it highlights the role of Law as an important institution to lead society to democratically elected objectives.